The Virulence Factor Macrophage Infectivity Potentiator (Mip) Influences Branched-Chain Amino Acid Metabolism and Pathogenicity of Legionella pneumophila - Fabian Nikolka; Mustafa Safa Karagöz; Mohamed Zakaria Nassef; Karsten Hiller; Michael Steinert; Thekla Cordes (Metabolites, 2023)
Legionella pneumophila (Lp) is a common etiological agent of bacterial pneumonia that causes Legionnaires’ disease (LD). The bacterial membrane-associated virulence factor macrophage infectivity potentiator (Mip) exhibits peptidyl-prolyl-cis/trans-isomerase (PPIase) activity and contributes to the intra- and extracellular pathogenicity of Lp. Though Mip influences disease outcome, little is known about the metabolic consequences of altered Mip activity during infections. Here, we established a metabolic workflow and applied mass spectrometry approaches to decipher how Mip activity influences metabolism and pathogenicity. Impaired Mip activity in genetically engineered Lp strains decreases intracellular replication in cellular infection assays, confirming the contribution of Mip for Lp pathogenicity. We observed that genetic and chemical alteration of Mip using the PPIase inhibitors rapamycin and FK506 induces metabolic reprogramming in Lp, specifically branched-chain amino acid (BCAA) metabolism. Rapamycin also inhibits PPIase activity of mammalian FK506 binding proteins, and we observed that rapamycin induces a distinct metabolic signature in human macrophages compared to bacteria, suggesting potential involvement of Mip in normal bacteria and in infection. Our metabolic studies link Mip to alterations in BCAA metabolism and may help to decipher novel disease mechanisms associated with LD.